2011
DOI: 10.1002/jmri.22662
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of hippocampal network connectivity correlates with cognitive improvement in mild alzheimer's disease patients treated with donepezil assessed by resting‐state fMRI

Abstract: Purpose To identify the neural correlates of cognitive improvement in mild AD subjects, following 12 weeks of donepezil treatment. Materials and Methods Resting-state functional connectivity MRI (R-fMRI) was used to measure the hippocampal functional connectivity (HFC) in 14 mild AD and 18 age-matched normal (CN) subjects. AD subjects were scanned at baseline and after donepezil treatment. CN subjects were scanned only at baseline as a reference to identify regions correlated or anticorrelated to the hippoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
60
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 40 publications
6
60
2
Order By: Relevance
“…This is often severe, affecting work, lifelong hobbies, and social life. Resting-state functional magnetic resonance imaging (R-fMRI) has been used extensively to diagnose AD Greicius et al, 2004;Li et al, 2002) and assess treatment (Goveas et al, 2011;Li et al, 2012;Sole-Padulles et al, 2013). These studies were based on the cross-correlation coefficient between the spontaneous blood oxygen leveldependent (BOLD) signals in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…This is often severe, affecting work, lifelong hobbies, and social life. Resting-state functional magnetic resonance imaging (R-fMRI) has been used extensively to diagnose AD Greicius et al, 2004;Li et al, 2002) and assess treatment (Goveas et al, 2011;Li et al, 2012;Sole-Padulles et al, 2013). These studies were based on the cross-correlation coefficient between the spontaneous blood oxygen leveldependent (BOLD) signals in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state activity changes will, in principle, reflect the downstream impact on brain networks of loss of synaptic function leading to neuronal death, and are likely to be sensitive to treatments that modulate synaptic function. Significant increases in functional connectivity of the hippocampal regions were found after 12 weeks of treatment with donepezil in a group of 14 patients with mild AD [52]. An enhancement of hippocampal functional connectivity with an extensive set of limbic and frontal structures was observed, including the parahippocampus, insula, lentiform nucleus, thalamus, posterior cingulate and middle and precentral frontal gyri.…”
Section: Functional Mrimentioning
confidence: 87%
“…There is a tendency toward diminished DMN activity in normal aging, MCI and dementia, pointing to reduced integrity of structures that are vulnerable to atrophy, beta amyloid deposition and reduced glucose metabolism [Hafkemeijer et al, 2012]. Studies that are performed on the resting state fMRI response to cholinergic interventions are restricted to AD patients and mainly indicate an increase in connectivity with DMN areas [Goveas et al, 2011; Li et al, 2012; Solé‐Padullés et al, 2013]. In another study, no effect on the DMN was found in both APOE ε4 carriers and non‐carriers [Wang et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there is also proof of more extensive effects of SSRIs on brain connectivity [Klaassens et al, 2015; Schaefer et al, 2014]. In AD patients, cholinergic stimulation induces alterations in connectivity for DMN regions [Goveas et al, 2011; Li et al, 2012; Solé‐Padullés et al, 2013], as well as networks involved in attention, control, and salience processing [Wang et al, 2014]. …”
Section: Introductionmentioning
confidence: 99%